2008
DOI: 10.1111/j.1365-294x.2007.03656.x
|View full text |Cite
|
Sign up to set email alerts
|

Around or across the Carpathians: colonization model of the Danube basin inferred from genetic diversification of stone loach (Barbatula barbatula) populations

Abstract: Despite increasing information about postglacial recolonization of European freshwater systems, very little is known about pre-Pleistocene history. We used data on the recent distribution and phylogenetic relationships of stone loach mitochondrial lineages to reconstruct the initial colonization pattern of the Danube river system, one of the most important refuges for European freshwater ichthyofauna. Fine-scale phylogeography of the Danubian populations revealed five highly divergent lineages of pre-Pleistoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…Although times of divergences were found older (i.e. Pliocene) than in T. souffia , a similar pattern was also found in the cold-adapted and rheophilic Barbatula barbatula , for which populations were maintained in the upstream portion of the rivers [105]. As a corollary, the thermophilic Rhodeus amarus , a species common in lotic and lentic habitats [106], has been documented to harbor rather homogenous populations along the Danube basin.…”
Section: Discussionmentioning
confidence: 65%
“…Although times of divergences were found older (i.e. Pliocene) than in T. souffia , a similar pattern was also found in the cold-adapted and rheophilic Barbatula barbatula , for which populations were maintained in the upstream portion of the rivers [105]. As a corollary, the thermophilic Rhodeus amarus , a species common in lotic and lentic habitats [106], has been documented to harbor rather homogenous populations along the Danube basin.…”
Section: Discussionmentioning
confidence: 65%
“…This premise is supported by the fact that in the case of other fish species, e.g. topmouth gudgeon - Pseudorasbora parva (Temminck & Schlegel, 1842), stone loach - Barbatula barbatula (Linnaeus, 1758), and grayling - Thymallus thymallus (Linnaeus, 1758), a similar or higher degree of differentiation among haplogroups is considered to be not more than subspecies level detachment [20], [74], [75]. In addition, some authors [76], [77] have suggested that the genetic distance of haplogroups must be greater than or equal to ten times the level of within-haplogroup differences to distinguish separate species.…”
Section: Discussionmentioning
confidence: 99%
“…Such phenomena are more likely to occur in organisms with limited dispersion ability and/or in organisms living in separated or narrowly connected habitats [15], [16], [17]. Many stream-dwelling fishes have specific environmental needs and therefore form discrete populations, not only between geographical areas with separated catchment systems, but also between closely related sites of the same catchment [18], [19], [20], [21]. These isolated fish populations may then genetically differentiate with time, although they may still maintain their similar morphological appearance and ecological function [22].…”
Section: Introductionmentioning
confidence: 99%
“…We expected strong genetic differentiation between the Danube and Rhine drainages, given that strong differentiation, and even cryptic taxa of European freshwater species are frequently discovered even in geographically close ranges, e.g. [13][16], [18], [32], [36], [42]–[45]. The star-like shape of the haplotype network [45][48], the highly significant deviations from selective neutrality, and the BSP estimates (Figure 4) all suggest an important and relatively recent increase in effective population size.…”
Section: Discussionmentioning
confidence: 99%
“…Local genetic variants and ESUs might harbor unique evolutionary potential, and provide the source of adaptation to future environmental change [9], [10]. These concerns are particularly relevant in freshwater systems, because several species show high levels of differentiation within their ranges, especially along the main catchments [11]–[13], and for species with a limited potential for overland dispersal [14][18]. Although existing works suggest that range losses should parallel the loss of genetic diversity [4]–[6], there is still little empirical information on the coupling of these processes, especially in freshwater species.…”
Section: Introductionmentioning
confidence: 99%